Perceiving Hysteria: Representations of the Liminal Position of Fibromyalgia in Unconventional Women’s Narratives - Alhadeff, Lara (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.